100 mV–1.2 V fully‐integrated DC–DC converters for thermal energy harvesting. Issue 6 (1st July 2013) - Bassi, Giovanni; Colalongo, Luigi; Richelli, Anna; Kovacs‐Vajna, Zsolt Miklós
Abstract : Two fully‐integrated DC/DC converters for energy harvesting applications are presented. The startup‐voltages of the converters are, respectively, 140 and 100 mV, the output voltage exceeds 1.2 V, with a power efficiency of about 20%. The architectures for boosting such extremely low voltages are based on an ultra‐low‐voltage oscillator cross connected to a capacitive converter. The overall circuits do not require any external components and can be fully integrated in a standard complementary metal oxide semiconductor low‐voltage technology. The converters have been designed in United Microelectronics Corporation 180 nm process.